2013
DOI: 10.1002/nbm.2917
|View full text |Cite
|
Sign up to set email alerts
|

Alterations of regional spontaneous neuronal activity and corresponding brain circuit changes during resting state in migraine without aura

Abstract: Although previous resting-state studies have reported abnormal functional cerebral changes in patients with migraine without aura (MwoA), few have focused on alterations in both regional spontaneous neuronal activity and corresponding brain circuits in MwoA patients during rest. Eighteen MwoA patients and 18 age- and gender-matched healthy controls (HC) were recruited in the current study. Baseline cerebral alterations were investigated using amplitude of low-frequency fluctuation (ALFF) and region of interest… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
91
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 99 publications
(103 citation statements)
references
References 84 publications
(122 reference statements)
12
91
0
Order By: Relevance
“…In addition to cortical thinning, the functional activity of both the ACC and the insular cortex was significantly reduced in patients with chronic migraine [60]. This result is in agreement with an 18 FDG-PET study demonstrating reduced metabolism of these brain regions in migraineurs [61], and an EEG study showing that migraineurs have decreased spontaneous cerebral activity, as measured by the amplitude of low-frequency fluctuation, in the rostral ACC and prefrontal cortex compared to healthy volunteers [72]. The insula has connections with the ACC in addition to the amygdala and the nucleus accumbens, and as such the reduced functionality of this brain region in migraine patients may serve to alter processing of both affect and reward.…”
Section: Anterior Cingulate Cortex In Pain and Rewardsupporting
confidence: 87%
“…In addition to cortical thinning, the functional activity of both the ACC and the insular cortex was significantly reduced in patients with chronic migraine [60]. This result is in agreement with an 18 FDG-PET study demonstrating reduced metabolism of these brain regions in migraineurs [61], and an EEG study showing that migraineurs have decreased spontaneous cerebral activity, as measured by the amplitude of low-frequency fluctuation, in the rostral ACC and prefrontal cortex compared to healthy volunteers [72]. The insula has connections with the ACC in addition to the amygdala and the nucleus accumbens, and as such the reduced functionality of this brain region in migraine patients may serve to alter processing of both affect and reward.…”
Section: Anterior Cingulate Cortex In Pain and Rewardsupporting
confidence: 87%
“…In previous neuroimaging studies, the ACC was the most consistently deactivated region in PET and fMRI migraine studies [35,36], and also had a decrease in gray matter [37,38]. Our research group verified that compared with healthy controls, migraineurs showed a significant decrease in ReHo values and amplitude of low-frequency fluctuation (ALFF) in the ACC [7,9], and showed aberrant functional connectivity which had the ACC involved [8,39]. In the present study, acupunctureinduced reduction in pain intensity ratings was negatively associated with increased average ReHo values in the ACC which illustrated that acupuncture treatment could promote pain reduction successfully by modulating the migraine-affected dysfunction region, the ACC, to some extent.…”
Section: The Similarities In Resting-state Brain Activity Evoked By Asupporting
confidence: 81%
“…Our research group involving migraine without aura patients showed that abnormal structure and function was possibly associated with an impaired pain processing and modulatory process, such as in the anterior cingulate cortex (ACC), insula, basal ganglia, thalamus, supplementary motor area (SMA), prefrontal cortex, etc. [7][8][9].…”
Section: Introductionmentioning
confidence: 99%
“…The results showed that these patients had altered RS spontaneous neuronal activity in pain-processing areas, including the left rostral anterior cingulated cortex, bilateral prefrontal cortex and right thalamus [32].…”
Section: Resting-state Functional Mri Connectivity In Migrainementioning
confidence: 99%